Density and distribution of nests of Mycetophylax simplex (Emery) (Hymenoptera, Formicidae) in areas with mobile dunes on the northern coast of Rio Grande do Sul, Brazil - Albuquerque,Emília Z. de (2005)
Studies on lower attines are scarce, especially on nesting and foraging ecology and behavior. This study aimed to contribute to the knowledge of an Attini in dunes ecosystems through the description of density and spatial distribution of Mycetophylax simplex (Emery, 1887) nests in a strip of mobile dunes in the Praia Grande beach, Torres, northern coast of Rio Grande do Sul, Brazil. The density and spatial distribution of nests were estimated in four plots of 2,500 m² each, in which were found 20, 209, 284 and 324 nests, with average densities of 0.01 nests/m², 0.09, 0.11 and 0.13 nests/m², respectively. The nests were found near to the vegetation and showed clumped distribution. The density and distribution pattern of the nests seem to be related to the availability of nesting places and foraging resources.